2023
DOI: 10.1021/acsami.2c19291
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Dependent Tumor Phototherapy Using Amino Acid-Engineered Chiral Phosphorene

Abstract: Phosphorene, also known as black phosphorus nanosheet (BPNS), has been investigated as a nanoagent for tumor therapy. However, promoting its intracellular accumulation while preventing the cytoplasmic decomposition remains challenging. Herein, for the first time, we propose a chiral BPNS designed through surface engineering based on amino acids with high biocompatibility and an abundant source for application in chirality-dependent tumor phototherapy based on its intracellular metabolism. The advantage of usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…However, chiral BPNS modified with cysteine can prolong their intracellular residence time, thereby enhancing their photothermal and photodynamic therapy efficacy on tumors. [73] D-Cys-BPNS exhibits higher cellular uptake and resistance to catabolism, thus resulting in enhanced ROS generation and stronger antitumor activity. The modification of chiral ligands offers a strategy to improve the stability and therapeutic efficacy of BPNS (Figure 8C).…”
Section: Tumor Therapiesmentioning
confidence: 99%
“…However, chiral BPNS modified with cysteine can prolong their intracellular residence time, thereby enhancing their photothermal and photodynamic therapy efficacy on tumors. [73] D-Cys-BPNS exhibits higher cellular uptake and resistance to catabolism, thus resulting in enhanced ROS generation and stronger antitumor activity. The modification of chiral ligands offers a strategy to improve the stability and therapeutic efficacy of BPNS (Figure 8C).…”
Section: Tumor Therapiesmentioning
confidence: 99%
“…This field of research has an extremely important role in promoting the development of life sciences and materials chemistry and has become an important topic in the field of chiral science. Chiral self-assembly can generate various functionalized materials with unique advantages that are widely used in fields of adjuvant therapy, biomimetic chemistry, catalysis, and molecular sensors. Currently, chiral nanomaterials are becoming the focus of fundamental research and various momentous technology applications due to their unparalleled physico-chemical properties, such as advanced circular dichroism (CD) and circularly polarized luminescence. Among them, rod-coil molecules have broad application prospects for supramolecular self-assembly owing to their accurate controlling of morphological nanostructures by adjusting molecular parameters such as the volume fraction of rod and coil groups, the cross-sectional area of flexible segments, and introducing lateral groups into rigid or flexible blocks. However, there are few studies regarding the influence of lateral groups with different positions on supramolecular chirality induction, especially related to the control of supramolecular nanostructures and aggregate morphologies by precisely adjusting the positions of lateral groups. Although individual studies have reported on chirality manipulation of supramolecular self-assemblies, it remains challenging to accurately control the position of lateral groups in rod-coil molecules to induce the chirality of aggregates for asymmetric synthesis and catalysis. …”
Section: Introductionmentioning
confidence: 99%
“…Conventional tumor nanomedicine has aroused extensive attention in cancer diagnosis and treatment because of the desirable blood circulation time and prior accumulation at the tumor tissue by enhanced permeability and retention (EPR) effect. , The rapid development of phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), based on nanotechnology holds tremendous promise because of its noninvasive nature, high selectivity, and negligible systemic cytotoxicity in emerging therapies. However, as with other monotherapies, phototherapy itself has inherent drawbacks, in which the partial pressure of oxygen in solid tumors is lower (only 10 mmHg) than in normal peripheral tissues (40–60 mmHg), seriously hampering the effect of oxygen-dependent PDT. , Moreover, PTT tends to induce upregulation of heat shock proteins in tumor tissue, resulting in rapid tumor tolerance and ultimately compromising the treatment effect. , Although the synergistic PDT/PTT could increase PDT efficiency by raising the blood flow rate to improve oxygen supply at the tumor site through hyperthermia and PDT can conversely induce heat-resistant tumor cell death, the undesirable penetration depth of excitation light and low specificity of phototheranostic reagents still hinder the synergistic treatment effect. , …”
Section: Introductionmentioning
confidence: 99%